Social Entrepreneurial Intention among Business Undergraduates: An Emerging Economy Perspective - Ayob, Noorseha; Yap, Ching Seng; Sapuan, Dewi Amat; Rashid, Md Zabid Abdul (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2013)
Social entrepreneurs are viewed as having the abilities to combat social and economic problems in which government, businesses, and non-profits may not be able to solve the problems alone. Consequently, with the collaboration among these sectors, more social enterprises can be established to create social values and development in a nation, specifically among the emerging economies. Therefore, it is timely to investigate what motivates undergraduates to develop social entrepreneurial intention. Drawing from the entrepreneurial models of Shapero and Sokol (1982) and Kruger and Brazeal (1994), this study aims to examine the social entrepreneurial intention among undergraduates from the perspective of an emerging economy. The proposed conceptual model differs from the existing entrepreneurial intention studies by adding the concepts of empathy and social entrepreneurship exposure as the antecedents to perceived desirability and perceived feasibility of social enterprising start-up, which in turn link to social entrepreneurial intention. Using the quota sampling technique, data were collected from 257 business and economics undergraduates from both public and private higher education institutions in Malaysia. The survey instrument was adapted from prior related studies, for instance, Davis (1983) for empathy; Shapero and Sokol (1982) for social entrepreneurship exposure; Krueger (1993) for perceived desirability and perceived feasibility; and Chen et al. (1998) for social entrepreneurial intention. Partial least squares path modelling was used to analyze the hypothesized relationships in the proposed conceptual framework. It is hoped that the findings of this study will shed light on the existing literature of social entrepreneurship, specifically the social entrepreneurial intention studies from the emerging economies perspective.